Transglutaminase Regulation of Cell Function - Eckert, Richard L. (American Physiological Society, 2014)
Transglutaminases (TGs) are multifunctional proteins having enzymatic and scaffolding functions that participate in regulation of cell fate in a wide range of cellular systems and are implicated to have roles in development of disease. This review highlights the mechanism of action of these proteins with respect to their structure, impact on cell differentiation and survival, role in cancer development and progression, and function in signal transduction. We also discuss the mechanisms whereby TG level is controlled and how TGs control downstream targets. The studies described herein begin to clarify the physiological roles of TGs in both normal biology and disease states.